ANTIOXIDANT EFFECT OF MORINGA (Moringa oleifera) LEAF ETHANOL EXTRACT ON SPERMATOGENESIS IN OLD WISTAR RATS (Rattus norvegicus) - Luh Putu Widiastini (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Infertility is the failure of pregnancy after regular sexual intercourse for 6-12 months without contraception. Infertility in man is primarily caused by damaged sperm production, for example, impairments in the spermatogenesis process, low spermatozoa concentrations, morphological factors, and abnormal sperm motility. The purpose of this study is to ascertain the antioxidant effect of moringa (Moringa oleifera) leaves ethanol extract on spermatogenesis (spermatogonia, spermatocytes, and spermatids counts) in old Wistar rats (Rattus norvegicus). This study took healthy old Wistar rats aged 18-19 months with a body weight of 200-250 g and with no physical disabilities. A total of 36 was Wistar rats divided into two groups, namely the treatment group (supplied with Moringa leaf ethanol extract of 50 mg/kgBW/ and 0.5% Carboxymethyl cellulose (CMC) of 0.5 mL per day) and the control group (only with 0.5% CMC of 0.5 mL per day) for 30 days. The results showed that there was a significant difference in the spermatogonia, spermatocyte, and spermatid counts between the group treated with Moringa leaf ethanol extract and the control group, resulting in a p-value of 0.000. Therefore, it can be concluded that Moringa leaf ethanol extract had a significant influence on the spermatogonia, spermatocyte, and spermatid counts in old Wistar rats.